DEBAT DAN ARGUMEN (HAKIKAT, RAGAM, DAN STRATEGI) - Jazeri, M. (Jurnal Bahasa Lingua Scientia, 2010)
Debate is arguing for certain topic with different  opinion or claim between affirmative team and negative team.  Seing from its elements, argument can be analyzed through two models; traditional argument model and Toulmin argument model. Traditional model is classified into four lay outs, namely (1) simple layout, (2) complex layout, (3) chain layout, and (4) compound layout.  Toulmin model is classified into five layouts, namely  layout I, layout II, layout III, layout IV, and layout V. Seing from its fallacy, the fallacy of argument is categorized into linguistics fallacy and relevance fallacy. Linguistics fallacies are equivoc term, amfiboly term, composition fallacy, devision fallacy, and accent fallacy. While relevance fallacies are argumentum ad hominem, argumentum ad verecundian, argumentum ad baculum, argumentum ad populum, argumentum ad misericordian, post hoc propter hoc, petitio principi, argumentum ad ignorantiam, dan ignoratio elenchi.